Situs inversus with atrial septal defect and pulmonary stenosis presenting as cortical blindness (Indian Journal of Case Reports, 2019)
Cortical blindness is a rare form of blindness characterized by the normal anterior visual afferent system. Cerebrovascular diseases, tumor involving bilateral occipital lobe, cardiac surgery or cerebral angiography are common causes for cortical blindness. Some cases may be associated with denial of blindness when it is called Anton syndrome. We came across a 9-year-old male child presenting to us for evaluation of blindness which turned out to be cortical blindness after the examination. EEG and VEP were consistent with cortical blindness with MRI showing parieto-occipital lobe signal intensity alterations. Evaluation for the cause of cortical blindness led to the diagnosis of situs inversus in the patient with an atrial septal defect. The patient had an episode of dehydration due to gastroenteritis which resulted in vascular compromise thereby leading to hypoxic damage to the brain and cortical blindness. Presentation of cortical blindness in a patient of situs inversus is unique and hence being reported.